Ovarian cancer: Status of homologous recombination pathway as a predictor of drug response. (May 2016) - De Picciotto, Nicolas; Cacheux, Wulfran; Roth, Arnaud; Chappuis, Pierre O.; Labidi-Galy, S. Intidhar
Abstract: Epithelial ovarian cancer (EOC), particularly high-grade serous subtype, is associated with germline mutations in BRCA1/BRCA2 genes in up to 20% of the patients. BRCA1/BRCA2 proteins are important components of the homologous recombination (HR) pathway, a vital DNA repair process that protects the genome from double-strand DNA damage. Recent studies revealed frequent somatic mutations of BRCA1/BRCA2 and hypermethylation of the promoter of BRCA1 in EOC, in addition to germline mutations. Comparison of DNA copy number changes in tumors with or without BRCA1/BRCA2 alterations, lead to the identification of several signatures that detect HR pathway defects, here named "HRness". These signatures predict platinum-sensitivity and survival in EOC, as it was previously shown for germline mutations of BRCA1/BRCA2 . They are currently investigated in clinical trials as potential predictive biomarker for response to poly(ADP- ribose) polymerase inhibitors.